Hubungan Derajat Keasaman (pH) Saliva dengan Jumlah Karies Gigi Pada Pasien Di Siloam Hospital Lippo Village Karawaci Tangerang - Pariati; Dwi Rezki Aulyah; Ayu Wijaya; Surya Irayani Yunus; Heny Ratnawati (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2026)
One of the important components of saliva that plays a role in the development of caries is the acidity level, or pH. Normal salivary pH ranges from 5.6–7.0, with an average of 6.7. If salivary pH is below normal, the oral environment becomes more acidic, supporting the growth of acidogenic bacteria such as Streptococcus mutans and Lactobacillus, which contribute to caries formation. This study aimed to determine the relationship between salivary acidity (pH) and the number of caries in patients at Siloam Hospital Lippo Village Karawaci Tangerang. This study was an analytical survey with a cross-sectional design. The study population was all patients at the Dental Clinic of Siloam Hospital Lippo Village Karawaci Tangerang, with a sample of 30 individuals selected using purposive sampling according to inclusion and exclusion criteria. Data were collected through observation (salivary pH and caries counts) and documentation. They were then processed and analyzed using the Kendall's tau-b test with a 95% confidence level (α = 0.05) using Microsoft Excel 2024 and IBM SPSS version 27. The results showed that patients' salivary pH tended to be alkaline with low caries counts, and there was a significant relationship between salivary pH and caries counts. Patients are advised to maintain a healthy lifestyle and oral hygiene, medical personnel to strengthen education and regular check-ups, and researchers to integrate salivary pH testing as part of dental health screening.